The Impact of IFN-g; Receptor on SLPI Expression in Active Tuberculosis: Association with Disease Severity - Tateosian, Nancy Liliana (2014)
Interferon (IFN)-g displays a critical role in tuberculosis (TB), modulating the innate and adaptive immune responses. Previously, we reported that secretory leukocyte protease inhibitor (SLPI) is a pattern recognition receptor with anti-mycobacterial activity against Mycobacterium tuberculosis (Mtb). Herein, we determined whether IFN-g modulated the levels of SLPI in TB patients. Plasma levels of SLPI and IFN-g were studied in healthy donors (HDs) and TB patients. Peripheral blood mononuclear cells from HDs and patients with TB or defective IFN-g receptor 1* were stimulated with Mtb antigen and SLPI, and IFN-gR expression levels were measured. Both SLPI and IFN-g were significantly enhanced in plasma from those with TB compared with HDs. A direct association between SLPI levels and the severity of TB was detected. In addition, Mtb antigen stimulation decreased the SLPI produced by peripheral blood mononuclear cells from HDs, but not from TB or IFN-gR patients. Neutralization of IFN-g reversed the inhibition of SLPI induced by Mtb antigen in HDs, but not in TB patients. Furthermore, recombinant IFN-g was unable to modify the expression of SLPI in TB patients. Finally, IFN-gR expression was lower in TB compared with HD peripheral blood mononuclear cells. These results show that Mtb-induced IFN-g down-modulated SLPI levels by signaling through the IFNgR in HDs. This inhibitory mechanism was not observed in TB, probably because of the low expression of IFN-gR detected in these individuals. (Am J Pathol 2014, 184: 1e6